The effect of population growth on unemployment youth in Somalia - Mohamud, Yasmin Abdullahi; Marof, Aini Azeqa; Mohamed, Abdullahi Mohamud; Gure, Mohamed Mohamud (Human Resource Management Academic Research Society, 2023)
The primary aim of this study was to investigate the impact of population growth on unemployment in Somalia. Specific objectives included examining the effects of population growth, gross domestic product, and inflation on unemployment. The research adopted an empirical research design to establish empirical connections between these variables and the unemployment rate in Somalia. The Ordinary Least Squares (OLS) technique was used to calculate numerical estimates of coefficients in the econometric equation, as it is known for its simplicity and possession of the Best Linear Unbiased Estimator (BLUE) properties. The conduct the research, annual time-series data from the World Bank database and International Monetary Fund for the period 1985-2019 were utilized. The relationships between the independent variables (population growth, gross domestic product, and inflation) and the dependent variable (unemployment) were established using Ordinary Least-Squares (OLS) regression. The economic software EVIEWS was employed to estimate the values of the impact of population growth on unemployment. The findings of the study indicated that the inflation coefficient suggested that a $1 increase in inflation led to a 53% increase in unemployment. Additionally, all other variables showed a positive relationship with unemployment. Thus, the null hypothesis was accepted, signifying that inflation has a significant influence on unemployment.